2019
DOI: 10.1038/s41467-019-10369-9
|View full text |Cite
|
Sign up to set email alerts
|

LIF regulates CXCL9 in tumor-associated macrophages and prevents CD8+ T cell tumor-infiltration impairing anti-PD1 therapy

Abstract: Cancer response to immunotherapy depends on the infiltration of CD8 + T cells and the presence of tumor-associated macrophages within tumors. Still, little is known about the determinants of these factors. We show that LIF assumes a crucial role in the regulation of CD8 + T cell tumor infiltration, while promoting the presence of protumoral tumor-associated macrophages. We observe that the blockade of LIF in tumors expressing high levels of LIF decreases CD206, CD1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
143
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 181 publications
(160 citation statements)
references
References 40 publications
3
143
0
Order By: Relevance
“…In addition, in LIF À/À mice mammary gland involution is delayed and reduced apoptosis is seen, while mammary glands show precocious development during pregnancy, indicating that LIF also plays a crucial role in involution following weaning (7). Finally, LIF also has important immunosuppressive functions during embryo implantation by regulating the numbers and migration of macrophages, uterine natural killer cells, and eosinophils (8,9), and similar effects were observed in a very recent study showing that LIF prevents CD8 þ T-cell infiltration into the tumor while at the same time activating protumoral macrophage function in the tumor microenvironment thus enhancing the immunosuppressive nature of the tumor (10).…”
supporting
confidence: 61%
“…In addition, in LIF À/À mice mammary gland involution is delayed and reduced apoptosis is seen, while mammary glands show precocious development during pregnancy, indicating that LIF also plays a crucial role in involution following weaning (7). Finally, LIF also has important immunosuppressive functions during embryo implantation by regulating the numbers and migration of macrophages, uterine natural killer cells, and eosinophils (8,9), and similar effects were observed in a very recent study showing that LIF prevents CD8 þ T-cell infiltration into the tumor while at the same time activating protumoral macrophage function in the tumor microenvironment thus enhancing the immunosuppressive nature of the tumor (10).…”
supporting
confidence: 61%
“…In several tumor models, the pharmacological inhibition of PI3Kγ or the stimulation of NF-κB was able to synergize with ICB therapy to promote tumor regression [49][50][51][52]. Other studies showed that high expression by TAMs of the leukemia inhibitory factor (LIF), a member of the IL-6 family, triggers the epigenetic silencing of CXCL9, a chemo-attractant for CD8+ T cells, and LIF inhibition improved the efficacy of anti-PD-1 therapy [53]. Finally, several studies have described how TAMs also interfere with the correct recruitment and localization of CD8+ T cells within the tumor, thus precluding the efficacy of ICB therapy [54,55].…”
Section: Interaction Of Tams With Immune-checkpoint Blockade Therapymentioning
confidence: 99%
“…Analogous to CNTF, LIF signals through LIFRa and gp130 to induce JAK/STAT dependent gene transcription. It was first described as a suppressor of proliferation in a myeloid leukemia cell line, but has since been associated to functions in multiple peripheral organs (252)(253)(254)(255)(256)(257). In addition, LIF has been recognized as neuropoetic cytokine, regulating the differentiation and activation of multiple cell types in the CNS (258)(259)(260)(261)(262).…”
Section: Lifmentioning
confidence: 99%